The Relationship Between Neutrophil-to-Lymphocyte Ratio and Coronary Collateral Circulation. (May 2015) - Uysal, Onur Kadir; Turkoglu, Caner; Sahin, Durmus Yildiray; Duran, Mustafa; Yıldırım, Arafat; Elbasan, Zafer; Ozkan, Bugra; Tekin, Kamuran; Kunak, Aysegul Ulgen; Yilmaz, Yucel; Kaya, Mehmet Gungor; Gur, Mustafa; et al.
Neutrophil/lymphocyte ratio (NLR) has been proposed as a prognostic marker to determine systemic inflammatory response and atherosclerosis. Our aim was to determine the relationship between NLR and development of coronary collateral circulation (CCC) in patients with stable coronary artery disease (CAD). A total of 521 consecutive patients with stable CAD who underwent coronary angiography and documented total occlusion in one of those major coronary arteries were included in this study. Levels of fasting blood glucose, white blood cell, and NLR were significantly higher in patients with poor collateral than in those with good collateral. After multivariate analysis, high level of NLR was an independent predictor of CCC together with levels of fasting blood glucose. The receiver–operating characteristic analysis provided a cutoff value of 2.75 for NLR to predict poor CCC with 65% sensitivity and 68% specificity. We demonstrated an independent association between levels of NLR and development of CCC in patients with stable CAD.